O trabalho docente no espaço-tempo da hora-atividade nas escolas públicas estaduais do município de Almirante Tamandaré - Scholochuski , Virginia do Carmo Pabst (2018)
The subject of the investigation presented at this research was the teaching work during the activity-hour of the professors of the Paraná school state system. Its goal was to analyze how the time of the teaching job destined to the activity-hour is used by the professors at the state schools of Almirante Tamandaré county. Therefore, the question that we intended to answer was: how the time-space destined to perform the activity-hour by the professors has been used at the state public schools of Almirante Tamandaré county? To answer that, we started with the analysis of the Brazilian education, from the last two decades of the XX century until the current scenario, seeking to understand the context in which the activity-hour was conquered, its percentage increase and its recent kickback. It was also discussed about the teaching work according to the definition of work by Karl Marx (2013), as well as about the influence of the capitalist society on education. From the ideas of Nacarato et al. (1998) it was debated about the conditions of the teaching work in Brazil. It was also found the need to understand the meaning of the terminology activity-hour, seeking to get to know the legislation that supports its realization, its concept in the literature and among education professionals. The methodological approach chosen was the one from the quantitative research proposed by Minayo (2009), Moreira and Caleffe (2008), and Ludke and André (1986). The data gathering techniques used were: semi-structured interviews (with teachers and pedagogues), participative observation (of the time-space of the activity-hour) and documental analysis. In relation to the analysis and handling of the empirical and documental material collected, it was based on the content analysis proposed by Bardin (1979). To understand the reality of the teaching work during the activity-hour, we looked to investigate the two unique school institutions of Almirante Tamandaré county in Paraná that offers only the final years of Elementary School. The data evidenced terrible physical and structural conditions of the schools to perform the activity-hour. In relation to taking advantage of the time of the activity-hour, it was found that the teachers dedicate the greatest part of their work during this time-space to perform short-term activities related to lessons planning and paperwork bureaucracy embodied in their work routine, and that, they hardly study during the activity-hour. The pedagogue, on the other hand, was found overloaded with school activities and is not able to organize study and reflection sessions during the time-space of the activity-hour. It was also found that the kickback of the percentage of the activity-hour demotivated the teachers and increased the amount of work of these professionals, and that, to handle everything, they take their work home. Therefore, it was concluded that the activity-hour is not a benefit to the teachers, but, instead, a right guaranteed by law, conquered by the teachers through fights and resistances, and, among its main goals one can highlight: increase the work conditions for teachers and the teaching quality provided to the population